Evaluation of the Nutritional Status and Eating Behaviors of Young Children with Type 1 Diabetes and Healthy Peers: A Controlled Cross Sectional Study - Onal, Seda; Ucar, Aslı; Siklar, Zeynep; Berberoglu, Merih (My University, 2024)
Aim: Eating behaviors affect young children with type 1 diabetes mellitus (T1DM). The aim is to identify eating behaviors, and nutritional status in young children with T1DM and healthy peers and evaluate the effect of eating behaviors on glycemic control in children with T1DM. Material and Methods: The study was a single-center controlled cross-sectional study of young children with T1DM (n=33) (age<7 years) and healthy peers (n=31).The eating behaviors of the young children were examined through the Behavioral Pediatric Feeding Assessment Scale and the food consumption status was evaluated using a 3-day food record. Glycosilated hemoglobin (Hemoglobin A1c) values of the young children with T1DM were obtained from hospital records, and analyzed. Results: Young children with T1DM have higher energy, fiber, and cholesterol intake than their healthy peers. (p<0.05). The young children with T1DM eat more healthily and have fewer behavioral eating disorders than their healthy peers. Parents of children with T1DM reported feeling worse about the child’s nutrition. No relationship was found between eating behaviors and glycemic control. Conclusion: Because parents of preschool children with type 1 diabetes feel more anxiety about their child’s disease, behavioral observation techniques should be used to examine their eating behavior, glycemic control, and other factors that may affect nutritional management.
Keywords: Nutrition; young children; behavioral pediatric feeding assessment scale; type-1 diabetes; eating behaviors